Need for Improved Definition of ”Chronic Wounds” in Clinical Studies - Kyaw, B (2017)
The term “chronic wound” was first used in the literature in the 1950s, to refer to wounds that were difficult to heal or did not follow a normal healing process (1, 2). However, the term has met criticism for its uncertainty regarding the duration of chronicity (3). Various alternative terminologies have been suggested, such as hard-to-heal wounds, difficult to heal wounds, non-healing wounds and complex wounds (4, 5). “Chronic wounds” are commonly defined as “wounds that have not proceeded through an orderly and timely reparation to produce anatomic and functional integrity after 3 months” (6). However, Martin & Nunan (7) defined a “chronic wound” as a barrier defect that has not healed in 3 months, and Leaper & Durani (8) defined it as a wound that lacks a 20–40% reduction in size after 2–4 weeks of optimal treatment or when there is not complete healing after 6 weeks. Recent reviews have also highlighted the lack of consensus regarding the definition of a “chronic wound” and the need for further research in this area (9, 10).